MECHANISMS OF THE FORMATION OF INNOVATIVE INITIATIVES IN YOUTH WORLDVIEW WITHIN THE CONTEXT OF CONTEMPORARY SOCIAL THOUGHT - Abdurakhmonov Khasan Ibrokhimovich (The Conference Hub, 2025)
This article examines the mechanisms underlying the formation of innovative initiatives in the worldview of youth within the context of contemporary social thought. The study analyzes how socio-cultural transformations, globalization processes, digital environments, and modern educational paradigms influence young people’s perception of innovation, creativity, and social responsibility. Particular attention is given to the role of social institutions, cultural values, and individual agency in shaping youth readiness for innovative and initiative-driven activity. The research emphasizes that innovative initiatives emerge as a result of the interaction between personal motivation and external socio-cultural conditions. The findings highlight the importance of developing an integrated theoretical and methodological framework to foster sustainable innovative thinking and proactive behavior among youth in modern society.
Keywords: youth worldview, innovative initiatives, social thought, socio-cultural mechanisms, youth development, innovation, social transformation